2005
DOI: 10.1007/s10930-005-6748-6
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibodies Against Soybean Bowman-Birk Inhibitor Recognize the Protease-Reactive Loops

Abstract: Monoclonal antibodies against soybean Bowman-Birk protease inhibitor (BBI) have been generated and used to detect and quantify BBI in foods, soybean germplasm, and animal tissues and fluids. The purpose of this study was to determine the recognition sites of two monoclonal antibodies to BBI (mAb 238 and mAb 217) in relation to the protease-inhibitory sites of BBI. The results showed that (1) the binding of mAb 238 can be blocked by trypsin and that of mAb 217 by chymotrypsin; (2) the trypsin or chymotrypsin in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…We started from the mRNA of the anti-BBI cell line secreting the monoclonal mAb 238 previously characterized. 16,20,22 Then, monovalent (singlechain Fv, scFv) and multivalent (single-chain diabody, scDb) anti-BBI recombinant antibody fragments were developed using the principles of genetic engineering and protein design. Figure 1a contains the general strategy we used to clone and obtain each antibody construct as single recombinant proteins.…”
Section: ■ Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We started from the mRNA of the anti-BBI cell line secreting the monoclonal mAb 238 previously characterized. 16,20,22 Then, monovalent (singlechain Fv, scFv) and multivalent (single-chain diabody, scDb) anti-BBI recombinant antibody fragments were developed using the principles of genetic engineering and protein design. Figure 1a contains the general strategy we used to clone and obtain each antibody construct as single recombinant proteins.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Surprisingly, the advancement of recombinant antibody technology is under-represented in food research and industry, an area where there is a need for improved analytical and purification methodologies. 22,31 Just as soy consumption patterns vary greatly across the world, so too do cancer incidences. An inverse relationship between soybean intake and cancer incidence has been reported, with Asian countries where soy forms an important part of the diet, such as Japan, displaying the lowest incidences of cancer.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to mention that in this study, both trypsin inhibitory domains present in the BBI isoinhibitor were recognized by the antibody used, based on a previous study on the reactivity of the same BBI antibody (mAb 238). 26 Previous studies have shown that germination alone had an effect on trypsin inhibitory activity in soybeans. Mostafa and Rahma 27 found that germination of soybean seeds for 6 days reduced trypsin inhibitory activity by 32%, while Bau et al 28 showed that KTI and BBI degradation was enhanced if allowed to germinate for more than 4 days.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 98%
“…Mouse monoclonal antibodies against BBI have been raised laboriously using the hybridoma approach, allowing quantitative determination of BBI in soy protein mixtures (Brandon, Bates et al 1989;Seerama & Gowda, 1997;Mao et al, 2005) but the lack of probes and purification methodologies has impeded progress. To date, tedious and time consuming, multi-step chromatographic procedures have been the convention for BBI purification.…”
Section: Unsurprisingly In 1992 Bbi Gained Investigational New Drugmentioning
confidence: 99%